La lingüística forense en didáctica: análisis de la capacidad de reflexión metalingüística movilizada por maestros en formación - Giménez García, Roser (2025)
Metalinguistic reflection (MR) facilitates the analysis and explanation of the structure of language, the comprehension of linguistic functions and awareness in language use. Yet, it has repeatedly been observed that initial teacher training does not guarantee sound MR skills. From an academic task based on forensic linguistics, we carry out a deductive content analysis on 43 speculations, 123 erroneous analyses, and 111 irrelevant observations identified in 25 papers written by trainee teachers , as indicators of deficiencies in their MR skills. We identify, mainly, confusions and incorrect uses of linguistic terminology, unfounded statements and personal assessments of the use of certain linguistic features. The analysis demonstrates the need to promote MR activities in trainee teacher and highlights the contributions of forensic linguistics in the designs of these exercises, given the lack of deep understanding of linguistic phenomena among future teachers shown by the results.